A novel, simple, and quick plate assay to screen silicolytic bacteria and silicase production using different substrates. (February 2022) - Kaur, Prabhjot; Sharma, Anjali; Bhardwaj, Nishi Kant; Singh, Amarjit; Dalal, Sunita; Sharma, Jitender
Abstract: Silicase helps in dissolving silica by catalyzing the cleavage of SiO and SiC bonds to form silicic acid. It belongs to carbonic anhydrases owing to its highest structural homology. Potential applications of silicase are wide and diverse ranging from e-waste remediation to tailoring nanochips and bio-desilication of rice straw for its utilization as substrate for biofuels production. Herein, a soil bacterium was isolated and screened for its ability to produce silicase. A simple and quick screening method for silicolytic bacteria was established. Different agro-residues including rice straw, wheat straw and bagasse along with silicon dioxide and magnesium trisilicate were investigated for their use as substrate. Silicase activity was found to be the highest for rice straw as a substrate since it has the highest silica content among other agro-residues. FTIR analysis of all production media showed silica dissolution before and after inoculation. Graphical abstract: Unlabelled Image Highlights: A quick and improved screening plate method for bacterial silicase production Nutrient agar supplemented with glucose and silicate provides the quickest screening. Silicase can be produced using agro-residues as well as synthetic silicate minerals. Bacterial uptake of silicic acid during silicase production FTIR analysis confirmed the silicic acid formation.